Prediction Of Subsurface Subsidence For Longwall Mining Operations - Yi Luo (International Conference on Ground Control in Mining, 2000)
Subsurface strata movements and deformations associated with underground mining activities could cause problems to subsurface structures and water bodies. By incorporating the methods for surface subsidence prediction with the subsidence parameters derived from collected subsurface subsidence data, methods have been proposed for the prediction of final and dynamic subsurface movements and deformations induced by underground longwall mining. Two new' types of strata deformations in the field of subsidence research, vertical and total strains that could he useful in assessing subsidence influences to the subsurface structures and water bodies, have peen introduced.